Microbeam X-ray and Scanning Electron Microscopic Analyses on Sector-Banded Spherulites of Poly(p-dioxanone) Justified with Pixelated Iridescence - Woo, Eamor M.; Lin, Chia-Hui; Nagarajan, Selvaraj; Su, Chean-Cheng (Polymers, 2024)
Poly(p-dioxanone) (PPDO) is crystallized with amorphous poly(p-vinyl phenol) (PVPh) and tannic acid (TA) as co-diluents to regulate and induce dendritic-ringed PPDO spherulites, with spoke- or sector-bands, aiming for convenience of analyses on interior lamellar assembly. Morphologies and interior lamellar arrangement leading to the peculiar rings on individual dendrites are evaluated by using polarized-light microscopy (PLM) and scanning electron microscope (SEM). Combinatory microbeam small-/wide-angle X-ray scattering (SAXS/WAXS) analyses further confirm the unique assembly patterns in periodic cycles. Alternate gratings are packed with periodic ridges composed of feather-like branches and the valley is featured with some embossed textures. The periodic gratings in the ringed spokes resemble those in nature’s structured coloration and are proven to display light-interference iridescence.